Vaccination-related inquiries from government/health hotline callers or official website visitors in Nanjing city, 2018 - 2022: an analysis on work orders of a municipal health institution - Qimin HUANG; Yaqiong LIANG; Rongfeng ZHOU; Yuanyuan LI (Editorial Office of Chinese Journal of Public Health, 2024)
ObjectiveTo analyze the characteristics of vaccination-related inquiries from government/health hotline callers or official website visitors in Nanjing city during 2018 - 2022. MethodsFrom Nanjing Municipal Center for Disease Prevention and Control, we collected totally 1 525 work orders for vaccination-related inquiries from government 12345/health 12320 hotline callers or official website visitors in Nanjing city during 2018 - 2022 and conducted descriptive statistical analysis on those inquiries with SPSS18.0 software. ResultsDuring the 5-year period, the average monthly number of vaccination-related inquiries accepted by the institution was 25.42, with the year-specific highest monthly number of 47 (accounting for 78.33% of the total number in the year) in July of 2018, 7 (14.29%) in June and November of 2019, 11 (20.00%) in February of 2020, 227 (32.24%) in August of 2021, and 165 (25.11%) in December of 2022, respectively. The top three vaccines most frequently concerned by the inquirers were coronavirus disease 2019 (COVID-19) vaccine (with 1128 inquiries), human papillomavirus (HPV) vaccine (103), and rabies vaccine (72). Of all the inquiries about herpes zoster vaccine, a newly approved vaccine, 85.71% were concerns about the site, time, appointment process, and relevant document required for the inoculation of the vaccine. Of all the inquiries about COVID-19 vaccine, the other newly approved vaccine, 47.52% were concerns about the site, time, appointment process, and relevant document required for the inoculation of the vaccine. ConclusionVaccine safety issue and major health emergency may hinder the implementation of planned immunization and major adjustment in immunization procedures for mass vaccination may lead to short-term increase in the number of vaccination-related inquiries from the public. The main inquiry about newly approved vaccines is how to get vaccinated.